120 Reproductive Performance, Early Embryo Survival, Fetal Characteristics, and Tissue Fatty Acid Profiles of Sows Fed Linoleic or α-Linolenic Acid. (12th April 2022) - Shipman, Garrin; Lin, Xi; van Heugten, Eric
Abstract: The objective of this study was to determine the potential reproductive benefits of supplementing sows with linoleic (LA) or α-linolenic acid (α-LA) throughout the preceding lactation and subsequent gestation until 30 d post-rebreeding. Thirty-three second parity sows were allotted to either a control (0.88% LA, 0.10% α-LA), high LA (3.3% LA, 0.10% α-LA, ) or high α-LA (0.88% LA, 0.60% α-LA) diet fed throughout lactation and early gestation. At 30 d post-breeding, a subset of sows (n = 18) was harvested to determine embryo survival and fatty acid composition of reproductive and fetal tissues. Number of pigs weaned per litter ( P = 0.77) and litter average daily gain ( P = 0.34) did not differ among treatments; however, litters from sows supplemented with LA tended to be heavier at weaning ( P = 0.09; 55.3, 61.3, and 57.1 kg for control, LA, and α-LA, respectively). Sows supplemented with LA had higher embryo survival ( P < 0.01; 57.2, 79.5, and 58.7% for control, LA, and α-LA, respectively), heavier feto-placental units ( P < 0.01; 210.3, 279.4 and 235.0 g for control, LA, and α-LA, respectively), and elevated volume of allantoic fluid ( P < 0.01; 185.9, 247.9, and 200.8 mL for control, LA, and α-LA, respectively). Concentrations of EFA increased in maternal serum by the dietary EFA supplemented ( P < 0.05). Supplementation of LA did not impact linoleic acid or arachidonic acid concentrations in endometrium, chorioallantoic membrane, or fetus; however, α-LA increased ( P < 0.05) concentrations of α-linoleic acid in chorioallantoic membrane and eicosapentaenoic acid in serum and endometrium. Supplementation of LA, but not α-LA, throughout lactation and early subsequent gestation was beneficial for embryo survival. The lesser influence of dietary LA and α-LA in fetal tissues may be associated with the intake, transfer, and metabolism of EFA in the chorioallantoic membrane and endometrium.